Madness in Anglophone Caribbean Literature On the Edge (New Caribbean Studies, 2018)
This collection takes as its starting point the ubiquitous representation of various forms of mental illness, breakdown and psychopathology in Caribbean writing, and the fact that this topic has been relatively neglected in criticism, especially in Anglophone texts, apart from the scholarship devoted to Jean Rhys's Wide Sargasso Sea (1966). The contributions to this volume demonstrate that much remains to be done in rethinking the trope of "madness" across Caribbean literature by local and diaspora writers. This book asks how focusing on literary manifestations of apparent mental aberration can extend our understanding of Caribbean narrative and culture, and can help us to interrogate the norms that have been used to categorize art from the region, as well as the boundaries between notions of rationality, transcendence and insanity across cultures. .